Landscape complexity and elevation affect the effectiveness of a local pest-management practice - Katja Poveda; María F. Díaz; Saira Espinosa; Diana Obregon; Augusto Ramirez (Global Ecology and Conservation, 2019)
Farm-scale diversification practices have been proposed as a means to enhance crop protection, primarily by increasing the presence of beneficial arthropods. The effectiveness of diversification is often context-dependent. Diversification is typically most effective in simplified landscapes dominated by agricultural land, which tend to have a scarce natural enemy community. However, in some diversification practices such as ‘push-pull’ systems, the primary goal is to change the behavior of pests through stimuli that repel (or push) the pest away from the crop, while pulling them toward a trap crop (pull). In such cases where pest control is not dependent on the presence of natural enemies, but on the manipulation of the pest's behavior, it is unclear if local management practices are context-dependent. We tested if the effectiveness of a push-pull practice in a potato cropping system for decreasing pest damage and increasing crop yield depends on the landscape context. We chose 14 Andean potato farms that varied in the proportion of cropland at a 1 km radius scale. At each farm, we established one control and one push-pull plot and measured pest damage and yield. Our results show that the effectiveness of the push-pull practice was dependent on the pest pressure on the farm, the landscape context, and elevation. The higher the pest pressure on a farm, the more effective the push-pull system was at increasing yield and reducing pests, but only in complex landscapes. In simple landscapes, there was no benefit of using the push-pull system and the tendency was decreased yields relative to control systems. Interestingly, elevation also played an important role in affecting the effectiveness of the push-pull practice. At higher elevations, the push-pull system was more effective at reducing pests and increasing yields. Our results suggest that under circumstances that are more challenging for herbivores, such as higher elevation or landscapes with fewer host crops, behavior-modifying management practices are more effective at increasing yields. We suggest that while diversification practices based on top-down control (e.g. flowering strips) could be recommended for growers in simple or intermediate landscapes, diversification practices such as push-pull that are based on behavior modification may be more appropriate to increase productivity in complex landscapes. Keywords: Context dependency, Intercropping, Intermediate landscape hypothesis, Landscape complexity, Potato, Premnotrypes vorax, Tecia solanivora